COMPARATIVE ANALYSIS OF STOCK PRICES BEFORE AND AFTER THE COVID PANDEMIC IN PHARMACEUTICAL COMPANIES - Maya Syaula (International Journal of Management, Economic and Accounting, 2023)
The Capital Market is a place for investors to carry out activities for the movement of their assets. However, since the existence of the Covid-19 Pandemic, investors have become very careful and at the same time become worried about carrying out activities in it. This is an unfavorable impact on the development of the world capital market in Indonesia. The purpose of this research is to find out and analyze how stock prices compare before and after the Covid-19 pandemic. The sample used in this study are pharmaceutical sub-sector companies listed on the Indonesian stock exchange. The research method used is descriptive comparative research. With the data analysis technique using the paired sample t-test difference test. Based on the results of the analysis and testing carried out, it can be concluded that the stock price of pharmaceutical companies before the pandemic was 1105,819 and after the covid-19 pandemic it was 1005,0939. the standard deviation before the pandemic was 726,27883 and after the pandemic it was 601,27062. The results of the paired sample t-test show the results of the significance value of 0.000. Therefore the value of Sig 0.000 < from 0.05. Thus, it can be interpreted that there are significant differences in stock prices in pharmaceutical sub-sector companies before and after the COVID-19 pandemic.